Potential therapeutic targets from Mycobacterium abscessus (Mab): recently reported efforts towards the discovery of novel antibacterial agents to treat Mab infections. Issue 4 (24th March 2022) - Addison, William; Frederickson, Martyn; Coyne, Anthony G.; Abell, Chris
Abstract : Recently reported inhibitors developed against targets from Mycobacterium absecessus ( Mab ). Abstract : Mycobacterium abscessus ( Mab ) are rapidly growing mycobacteria that cause severe and persistent infections in both skin and lung tissues. Treatment regimens involve the extended usage of complex combinations of drugs, often leading to severe adverse side effects, particularly in immunocompromised patients. Current macrolide therapies are gradually proving to be less effective, largely due to emergence of antibiotic resistance; there is therefore an increasing need for the discovery of new antibacterials that are active against Mab . This review highlights recent research centred upon a number of potential therapeutic targets from Mab (Ag85C, ClpC1, GyrB, MmpL3 and TrmD), and discusses the various approaches used to discover small molecule inhibitors, in the search for future antibiotics for the treatment of Mab infections.